Pemanfaatan Aplikasi Tik Tok Bagi Mahasiswa dalam Pembelajaran Pendidikan Kewarganegaraan di Universitas PGRI Semarang - Mahendra, Irvan; Marzuqi, Yasir; Dewi Meilla Alvianti, Shintya (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study aims to see how the use of the Tik Tok application for students in learning citizenship education at PGRI Semarang University is one way to increase creativity in utilizing the latest learning media in accordance with the times and increase student creativity and interest in learning in following the ongoing learning process. This research is a qualitative descriptive study with the subject of 14 students of Physics semester 3, PGRI University Semarang. The results of the study show that 1) the Tik Tok application as a learning medium supports the learning process 2) the Tik Tok application as a learning medium for civic education materials gets a positive response from students. The conclusion of this research is that the Tik Tok application is an application that can be used as a learning medium in the learning process and this application also gets a positive response from students regarding its use as a learning medium for civic education materials